2018
DOI: 10.1002/2017jc012940
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Alteration Promotes Humic Acid Formation in Sediments: A Case Study of the Central Indian Ocean Basin

Abstract: Anomalously high concentrations of humic‐rich dissolved organic matter (DOM) in extant submarine hydrothermal vent plumes traveled far from source are increasingly being reported. This DOM, able to mobilize trace metals (e.g., Fe2+) has been hypothesized as originating from organic matter produced by thermogenic bacteria. To eliminate a possible abiogenic origin of this DOM, study is required of well‐preserved organic compounds that can be attributed to thermogenic bacteria. The Central Indian Ocean Basin (CIO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…If dissolved Fe bound to organic ligands causes extensive vertical and lateral transport of dissolved Fe in the abyssal Indian Ocean, there is a possibility that FOM370/440 could also be affected by the hydrothermal vents, because humic-like FDOM is likely a major Fe-binding organic ligand in the dark ocean ( Laglera and van den Berg, 2009 ; Yamashita et al, 2020 ). A few studies indicate that hydrothermal systems act as a sink of DOM ( Hawkes et al, 2016 ; Yang et al, 2017 ), while some studies indicate that the systems behave as a source of DOM ( Yang et al, 2012 ; Sarma et al, 2018 ). In this study, the regions were not found where both turbidity and FOM370/440 levels were high along the Leg 2 transect ( Figures 6L , 8A ).…”
Section: Discussionmentioning
confidence: 99%
“…If dissolved Fe bound to organic ligands causes extensive vertical and lateral transport of dissolved Fe in the abyssal Indian Ocean, there is a possibility that FOM370/440 could also be affected by the hydrothermal vents, because humic-like FDOM is likely a major Fe-binding organic ligand in the dark ocean ( Laglera and van den Berg, 2009 ; Yamashita et al, 2020 ). A few studies indicate that hydrothermal systems act as a sink of DOM ( Hawkes et al, 2016 ; Yang et al, 2017 ), while some studies indicate that the systems behave as a source of DOM ( Yang et al, 2012 ; Sarma et al, 2018 ). In this study, the regions were not found where both turbidity and FOM370/440 levels were high along the Leg 2 transect ( Figures 6L , 8A ).…”
Section: Discussionmentioning
confidence: 99%
“…Humic ligands form iron complexes of intermediate strength 13,14 , bracketed by stability constants of the stronger siderophores and weaker polysaccharides. All major sources of iron to the water column also supply humic-like material [15][16][17][18] , with terrestrial-derived humics often dominating iron complexation in estuarine and coastal waters 13,14 . Furthermore, the stability of iron-humic complexes allows iron to be transported long distances by ocean currents 19 .…”
mentioning
confidence: 99%
“…Intriguingly, a near‐Redfield ratio might indicate in situ organic synthesis by RuBisCO pathway in chemolithotrophs, rather than being a detrital signature. In situ production of organic matter by chemosynthetic processes in these sediments is well known by now (Das et al, , ; Sarma et al, ). An involvement of Fe 2+ and possibility of thermophilic microbes regulating the humic acid pool have been indicated in fracture zone areas of CIB (Sarma et al, ).…”
Section: Discussionmentioning
confidence: 94%
“…In situ production of organic matter by chemosynthetic processes in these sediments is well known by now (Das et al, , ; Sarma et al, ). An involvement of Fe 2+ and possibility of thermophilic microbes regulating the humic acid pool have been indicated in fracture zone areas of CIB (Sarma et al, ). A recent study in the Arabian Sea oxygen minimum zone has used a combination of community sequencing and isotope studies of sulfur (Fernandes et al, ).…”
Section: Discussionmentioning
confidence: 94%